Green roofs and its socio-culture benefits in Peninsular Malaysia - Hamzah Z.,; Ja’afar M.F.Z.,; Mat Sulaiman M.K.A., (Penerbit Universiti Kebangsaan Malaysia, 2017)
The contribution of green roofs to pressing environmental issues in urban areas is proven by much research to help mitigate problems like urban heat island effect, storm water runoff, thermal comfort, energy consumption, deterioration of air and water quality as well as loss of habitats. Green roofs also have a significant role to socio-cultural improvements of a place. The objective of this paper is to review the social and cultural benefits of green roofs that have become an increasingly popular architectural feature, particularly in Peninsular Malaysia. The methodology used is via literature and observations. Findings show that research into the behavioural sciences of green roofs is still lacking and further research in the context of Malaysia is pertinent.